A HEDONIC ANALYSIS OF TENGGER TYPICAL CHILI SAUCE (CASE STUDY IN NGADIWONO VILLAGE, TOSARI DISTRICT, PASURUAN REGENCY) - Siska Septiana; Dego Yusa Ali; Teti Estiasih; Neza Fadia Rayesa; Alia Fibrianingtyas; Nevara Latansya; Igoy Arya Bimo (Jurnal Pangan dan Agroindustri, 2023)
Habanero-type pepper (Capsicum chinense) is one of the main horticultural commodities in the Tengger mountains. These chilies is potential to be processed into ready-to-eat products. The development of this product is expected to improve the Tengger local economy. This study aims to determine the level of acceptance of Tengger typical chili sauce made from habanero-type pepper with and without the shrimp paste. A 5-point scale hedonic test was conducted to analyze the liking score of the original Tengger chili sauce, chili sauce with shrimp paste and commercial chili sauce as reference. 30 untrained panelists participated in this test. There was a significant difference in the liking scores especially on color attribute (p<0.05). Panelists gave lower acceptance scores to chili sauce with shrimp paste in color, aroma, and taste attributes. In general, the original Tengger chili sauce without the addition of shrimp paste is competitive with commercial chili sauce.